Relevance of Bharata Muni’s Natyashastra in the Digital Era - Chitaliya , Palak Parekh (Bodhi: An Interdisciplinary Journal, 2024)
Bharata Muni’s Natyashastra, an ancient Sanskrit treatise persists as a pivotal text even in the digital age. This study asserts that Natyashastra not only maintains its considerable academic and artistic significance but also contributes significantly to fostering creativity and nurturing cross-cultural dialogue in the contemporary digital context. The research employs a comprehensive methodology, including theoretical analysis, historical contextualization, and contemporary case studies, to explore how Natyashastra principles are utilized by digital platforms. These platforms craft immersive storytelling experiences and navigate diverse emotional responses among global audiences. Findings reveal that Natyashastra excels in facilitating cross-cultural understanding and enhancing artistic expression in the digital landscape. It transcends cultural boundaries, offering insights into multicultural interactions and promoting artistic innovation. The study underscores the relevance of integrating traditional artistic wisdom with digital advancements, impacting artistic practices, empathy, and cultural exchange on a global scale.